P439 Induction of endoscopic response, remission and ulcer-free endoscopy with upadacitinib is associated with improved quality of life in patients with Crohn's disease. (30th January 2023) - Panés, J; Louis, E; Bossuyt, P; Joshi, N; Lee, W J; Lacerda, A; Remple, V; Xuan, S; Loftus Jr., E V
Abstract: Background: Patients with Crohn's disease (CD) experience reduced quality of life (QoL), and disease-related impact on work productivity, contributing to a high disease burden. This study evaluated the association of achieving endoscopic outcomes at week 12 and associated QoL at week 52 in patients with CD treated with upadacitinib (UPA). Methods: This post-hoc analysis evaluated data from two Phase 3 UPA induction (U-EXCEED and U-EXCEL) trials and one maintenance (U-ENDURE) trial in patients with moderate to severe CD. Patients who responded to 12-week induction therapy with UPA (45 mg per day [QD]) in U-EXCEED or U-EXCEL and received maintenance therapy with UPA (15 or 30 mg QD) up to 52 weeks in U-ENDURE were included. Meaningful improvement in QoL outcomes (Inflammatory Bowel Disease Questionnaire [IBDQ] remission ≥170, IBDQ response increase ≥16, Functional Assessment of Chronic Illness Therapy – Fatigue [FACIT-F] response increase ≥9, Short Form 36 [SF-36] Physical Component Score [PCS] and Mental Component Score [MCS] change ≥5, and Work Productivity and Activity Impairment Questionnaire [WPAI] change ≥7%) was evaluated at week 52 and compared between patients who achieved endoscopic response, endoscopic remission and ulcer-free endoscopy (absence of ulceration) at week 12 and those who did not using Chi-square test. Results: Of 337 clinical responders included in the analyses, 152 (45.1%), 87 (25.8%), and 75 (22.2%) patients achieved endoscopic response, endoscopic remission, and ulcer-free endoscopy, respectively, at the end of induction. Significantly more patients who achieved an endoscopic response at end of induction (vs those who did not) attained a meaningful improvement in PROs by week 52 (IBDQ remission, 52.6% vs 30.3%; IBDQ response, 56.6% vs 36.8%; FACIT-F response, 46.7% vs 25.9%; SF-36 PCS 49.3% vs 30.8% and MCS 39.5% vs 25.9%; all P≤0.01, Table 1). Additionally, patients who achieved endoscopic response (vs those who did not) at the end of induction were more likely to attain meaningful improvement in WPAI overall work impairment by week 52 (47.1% vs 26.5%, P≤0.01, Table 1). Similar findings were observed in patients who achieved endoscopic remission (P≤0.01, Table 1) and ulcer-free endoscopy (P≤0.05, Table 1) vs those who did not at end of induction. Conclusion: Achieving endoscopic outcomes at end of induction treatment was associated with meaningful improvement in quality of life and overall work productivity at 52 weeks for patients with CD receiving UPA. Endoscopic remission and ulcer-free endoscopy were associated with very similar long-term benefit.